Kajian Hukum Terhadap Perselisihan Pemutusan Hubungan Kerja Secara Sepihak Pada Perusahaan - Taufiq, Muchamad; Hidayat, Zainul (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2011)
Invite to invite number Republic of Indonesia: 2 year 2004 about connection disagreement industrial mention, " work connection severance disagreement that disagreement because inexistence same as opinion hits work connection terminating that done by one of the parties" . Confirmed also in section 3 that, " connection disagreement industrial obligatory strived for the completion beforehand pass negotiation bipartite upon mutual consensus to achieve agreement" . Disagreement ends in PHK most often if in character unilateral that is caused by boss and worker, but importantest analysis to PHK caused by boss because bot rarely laid worker position as weak side, in pressure, treated inequitable, also inhuman. This watchfulness lifts troubleshoot about procedure PHK with legal consequences on phk unilateral that caused by boss. This watchfulness uses to approach law and regulation because this watchfulness to focus in applications and analysis towards law and regulation related to work connection severance disagreement. Law ingredient that used in this watchfulness covers primary law ingredient that is law and regulation related work connection severance disagreement, while secondary law ingredient covers books or literature related to work connection severance disagreement and to working. Law ingredient collecting technique passes book study, the essentials is registerred by using card system. method that used in law ingredient collecting snowball method. Ingredient analysis is done to conclude deductively. use premis major, furthermore applied in unilateral work connection severance disagreement event in companies â€œpremis minorâ€, furthermore pulled konklusi-. Watchfulness to detect, realize, with analyze procedure PHK at company and legal consequences PHK in company. watchfulness benefit theoretically be evaluation towards procedure PHK found in invite to invite Number : 12 year 1964 so that can be made base law source repair to employed and the practise benefit reality law protection for worker so that created certainty principality and law justice